First-in-Human Intraoperative MRI Coil for High Resolution Imaging During Transsphenoidal Surgery. (16th November 2020) - Hogan, Elizabeth; Alvarez, Reinier; Talagala, Lalith; Sarlls, Joelle; Merkle, Hellmut; Koretsky, Alan; Scott, Gretchen; Butman, John A; Chittiboina, Prashant
Abstract: INTRODUCTION: Failure of remission following transsphenoidal surgery (TSS) for pituitary adenomas range from 20–80% with recurrences in up to 7–35% of successful cases. The causes of failures include inability to visualize small adenomas, the true extent of large adenomas or invasion of parasellar structures. Improved pre-operative and intraoperative-MRI (iMRI) can lead to better outcomes. However, high-resolution imaging of the sella is limited by low signal-to-noise ratio (SNR) even in expensive higher strength MRI machines. Surface coils can improve SNR significantly in the adjacent structures. METHODS: We designed a first-in-human interventional trial (NCT03678389) to evaluate the feasibility of ESC use during TSS at the NIH Clinical Center in Bethesda. Patients >18 years of age with a known or suspected pituitary tumor that requires surgical resection were included. Main outcomes are feasibility (ability to obtain clinically useful images within 90 minutes of initiating ESC portion of surgery) and safety. Safety outcomes include local trauma or other unanticipated safety issues. RESULTS: Of the 6 patients enrolled; imaging with ESC was completed in 4. Following initial sublabial approach, sphenoid sinus was cleared, and the ESC inserted under sterile precautions in 5 patients. In all patients, we successfully inserted the ESC to the optimal position at the sellar face, with technical problems hindering imaging of one patient. We detected a breach of sterile sheath in Patient-1 that led to durable change in sterile sheathing practice. Except Patient-1, all patients underwent <90 minutes of iMRI scan time. We discovered no evidence of local trauma or other unanticipated problems. High-resolution imaging with ESC allowed us to detect MRI-negative microadenoma and other anatomic details not visible on standard preoperative imaging. CONCLUSION: We find that the ESC is a safe intra-operative surgical adjunct. The high-resolution imaging with ESC can detect otherwise MRI-negative microadenomas, and parasellar anatomic structures not apparent on pre-operative imaging.